Technological innovation and agricultural productivity in Nigeria amidst oil transition: ARDL analysis - Joel T. Adeyemo; Adel Ahmed; Dominic T. Abaver; Hosam Alden Riyadh; Mosab I. Tabash; Adedoyin Isola Lawal (Economies, 2024)
In contemporary discourse, Nigeria's reliance on its oil sector is proving insufficient for sustained economic growth. The volatility of oil prices, geopolitical tensions, technological advancements, and environmental sustainability concerns have exposed the vulnerabilities of an oil-dependent economy, emphasizing the need for diversification and a renewed focus on agriculture. This study investigates the relationship between technological innovation and agricultural productivity in Nigeria, contrasting it with the oil sector. Using the ARDL estimation technique, our findings reveal a significant negative influence of immediate lagged agricultural productivity (AGTFP(-1)), indicating technological constraints. Technological innovation, proxied by TFP, shows a substantial impact on agricultural productivity, with a negative long-term effect (-90.71) but a positive, though insignificant, impact on agricultural output (0.0034). The comparative analysis underscores that the agricultural sector tends to benefit more from technological innovation than the oil sector. This highlights the critical need to prioritize technological advancements in agriculture to drive sustainable growth and economic resilience in Nigeria.
Keywords: 330; agricultural productivity; ARDL; Nigeria; oil; technological innovation